2020
DOI: 10.3390/ijerph17217723
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Gas and Chimney Biomass Stoves for Reducing Household Air Pollution Pregnancy Exposure in Guatemala: Sociodemographic Effect Modifiers

Abstract: Household air pollution (HAP) due to solid fuel use during pregnancy is associated with adverse birth outcomes. The real-life effectiveness of clean cooking interventions has been disappointing overall yet variable, but the sociodemographic determinants are not well described. We measured personal 24-h PM2.5 (particulate matter <2.5 µm in aerodynamic diameter) thrice in pregnant women (n = 218) gravimetrically with Teflon filter, impactor, and personal pump setups. To estimate the effectiveness of owning ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
2
12
0
1
Order By: Relevance
“…Similarly, there was a 33% reduction in personal exposure to PM 2.5 in pregnant women associated with using LPG for cooking instead of biomass in an effectiveness study in rural Mexico [ 26 ]. Another study in Guatemala showed similar statistics, supporting the health benefits of LPG stove usage when compared to more traditional methods [ 25 ]. Despite this significant finding that LPG stoves can reduce the level of PM 2.5 in a household, PM concentrations in our study still exceeded the WHO recommendation for an annual mean of 35 μg/m 3 and a 24 h mean of 25 μg/m 3 .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Similarly, there was a 33% reduction in personal exposure to PM 2.5 in pregnant women associated with using LPG for cooking instead of biomass in an effectiveness study in rural Mexico [ 26 ]. Another study in Guatemala showed similar statistics, supporting the health benefits of LPG stove usage when compared to more traditional methods [ 25 ]. Despite this significant finding that LPG stoves can reduce the level of PM 2.5 in a household, PM concentrations in our study still exceeded the WHO recommendation for an annual mean of 35 μg/m 3 and a 24 h mean of 25 μg/m 3 .…”
Section: Discussionmentioning
confidence: 77%
“…It is likely that an LPG stove can help lower indoor PM 2.5 levels to the WHO target of 10 μg/m 3 , which is highly favorable compared to other speculated interventions with improved biomass cookstoves [ 22 , 24 ]. Two studies have estimated a ≈33% reduction in personal exposure to PM 2.5 in pregnant women associated with using LPG fuels instead of biomass fuels [ 25 , 26 ]. Likewise, studies have shown that CO concentrations decrease with the use of LPG stoves [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Rwanda, a trial of rocket-style cookstoves and water filters reported median exposures of 158 and 146 μg/m 3 in the control and intervention arms, respectively, for the primary cook (compared to 80 μg/m 3 in the control arm and 28-34 μg/m 3 post-intervention for the HAPIN site in Rwanda) (Kirby et al 2019). A study of pregnant women in Guatemala reported median exposures of 148 μg/m 3 for open fire users and 55 μg/m 3 for those using LPG (compared to 94-98 μg/m 3 in the control arm and 23-24 μg/m 3 in the intervention arm for the HAPIN site in Guatemala) (Grajeda et al 2020), while in India the Tamil Nadu Air Pollution and Health Effects (TAPHE) cohort study of pregnant women estimated median PM 2.5 exposures of 75 μg/m 3 for biomass stove users and 46 μg/m 3 for those using primarily LPG (compared to 67-68 and 25-29 μg/m 3 in the control and intervention arms, respectively, for the HAPIN site in Tamil Nadu, India) (Balakrishnan et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…1 Individuals affected by BSE mainly women who use biomass for cooking in underdeveloped rural areas; these individuals have relatively lower socioeconomic status. [5][6][7][8] BSE has received insufficient attention. [9][10][11] For example, among users of Douyin (a popular social media service in China), there are currently 198 accounts that promote smoking cessation-related content; by contrast, only one professional account addresses the risks of biomass smoke pollution.…”
Section: Introductionmentioning
confidence: 99%